Motivators and Barriers for Pursuing Postgraduate Programs in Pharmacy Practice Among Pharmacy Interns in Saudi Arabia - Abdullah M. Alhammad PharmD; Majidah Aljohani MSc; Bana Almadi PharmD; Yazeed Ghawaa MSc; Mansour Almuqbil PhD; Ghazwa B. Korayem PharmD; Hisham A. Badreldin PharmD; Ohoud Aljuhani PharmD; Nora A. Kalagi PhD; Yahya M. K. Tawfik PharmD; Mohammad H. Aljawadi PhD; Yousif A. Asiri PhD; et al. (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Postgraduate programs (PGPs) in pharmacy practice have gained significant importance in recent years, reflecting the evolving roles and expanding responsibilities of pharmacists globally. Understanding the factors that influence the decision to pursue such programs is essential for workforce development and educational planning. This study aimed to assess the motivations and barriers influencing pharmacy interns in Saudi Arabia to pursue PGPs in pharmacy practice. This cross-sectional study was conducted from December 2019 to March 2020 and utilized a validated questionnaire distributed electronically to pharmacy interns (sixth-year pharmacy students) across 3 major pharmacy schools in Saudi Arabia. Data were analyzed using descriptive statistics, chi-square, and Fisher’s exact tests, with a significance level set at a P -value of less than .05. Of the 247 pharmacy interns invited, 157 (62%) completed the survey. Most respondents were female (82.8%) and had an average of 3 clinical and 2 nonclinical advanced pharmacy practice experiences. Approximately 20% intended to pursue PGPs immediately after graduation, while 60% would consider them later. Preferred career paths included hospital pharmacy (31.85%) and regulatory bodies (24.84%). The decision to pursue PGPs in pharmacy practice was influenced by PGP orientation during school, either positively or negatively. The primary motivator cited was the need for further training for future positions, whereas high competition was the most significant barrier. These findings offer valuable insight into pharmacy interns’ perspectives on PGPs, highlighting key motivators and barriers. This understanding can inform future educational strategies and stakeholder efforts aimed at supporting pharmacy interns’ career planning and addressing workforce development needs in pharmacy practice.